Pengaruh Penggunaan Media Pembelajaran Berbasis Quizizz Terhadap Minat Belajar Mahasiswa Pendidikan Matematika - Lilik Nur Susilowati; Dewi Putri Yanti; Moh. Syadidul Itqan (CV Edujavare Publishing, 2025)
In the learning process, creating an environment or learning atmosphere that stimulates active participation of students is very important, because students will find it easier to understand the concepts taught when they are actively involved. This study aims to determine the extent to which learning media using the quizizz application affects mathematics education students. This study uses a quantitative method with a survey approach on 37 students, data was collected through a questionnaire. The results of the validity and reliability tests of the instrument show the feasibility of the data. The residual normality test indicates a normal data distribution. However, the linearity test revealed that the relationship between learning interest and Quizizz results was non-linear. Simple linear regression analysis shows that the use of Quizizz does not have a significant effect on students' learning interest (Sig. 0.408> 0.05). The coefficient of determination (R2) of 0.020 indicates that only 2.0% of the variation in learning interest can be explained by Quizizz, confirming that the linear model is not suitable to describe this relationship. Thus, it is concluded that Quizizz-based learning media does not significantly affect students' learning interest in the context of the linear model tested